Food Neophobia, Odor and Taste Sensitivity, and Overall Flavor Perception in Food - Sharon Puleo; Ada Braghieri; Corrado Pacelli; Alessandra Bendini; Tullia Gallina Toschi; Luisa Torri; Maria Piochi; Rossella Di Monaco (Foods, 2021)
Smell, which allows us to gather information about the hedonic value of an odor, is affected by many factors. This study aimed to assess the relationship among individual factors, odor sensitivity, and enjoyment, and to evaluate how overall flavor perception and liking in actual food samples are affected by odor sensitivity. A total of 749 subjects, from four different Italian regions, participated in the study. The olfactory capabilities test on four odors (anise, banana, mint, and pine), as well as PROP (6-n-prpyl-2-thiouracil) status and food neophobia were assessed. The subjects were clustered into three groups of odor sensitivity, based on the perceived intensity of anise. The liking and intensity of the overall flavor were evaluated for four chocolate puddings with increasing sweetness (C1, C2, C3, and C4). The individual variables significantly affected the perceived intensity and liking of the odors. Even if all of the odor sensitivity groups perceived the more intensely flavored samples as the C1 and C4 chocolate puddings, the high-sensitivity group scored the global flavor of all of the samples as more intense than the low-sensitivity group. The low-sensitive subjects evaluated the liking of the sweeter samples with higher scores than the moderate-sensitive subjects, whereas the high-sensitive subjects gave intermediate scores. In conclusion, odor sensitivity plays a pivotal role in the perception and liking of real food products; this has to be taken into account in the formulation of new products, suitable for particular categories with reduced olfactory abilities.